2012
DOI: 10.1128/jb.00056-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analyses of 17 Clinical Isolates of Gardnerella vaginalis Provide Evidence of Multiple Genetically Isolated Clades Consistent with Subspeciation into Genovars

Abstract: Gardnerella vaginalis is associated with a spectrum of clinical conditions, suggesting high degrees of genetic heterogeneity among stains. Seventeen G. vaginalis isolates were subjected to a battery of comparative genomic analyses to determine their level of relatedness. For each measure, the degree of difference among the G. vaginalis strains was the highest observed among 23 pathogenic bacterial species for which at least eight genomes are available. Genome sizes ranged from 1.491 to 1.716 Mb; GC contents ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
216
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(242 citation statements)
references
References 76 publications
20
216
1
5
Order By: Relevance
“…However, when mapped onto whole-genome phylogenies ( Fig. 2B and SI Materials and Methods), these variants differentiate between significantly diverged "genovars" within the G. vaginalis species (21). The functional classifications of clade-specific genes are largely redundant but transporters, membrane proteins, and toxin-antitoxin systems appear overrepresented in G2 variant genomes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…However, when mapped onto whole-genome phylogenies ( Fig. 2B and SI Materials and Methods), these variants differentiate between significantly diverged "genovars" within the G. vaginalis species (21). The functional classifications of clade-specific genes are largely redundant but transporters, membrane proteins, and toxin-antitoxin systems appear overrepresented in G2 variant genomes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of G. vaginalis have found that virulent strains are superior to commensal strains in their ability to adhere to both vaginal (15) and cervical (16) epithelium, which may contribute to the correlated concentrations we observed at these sites. In addition, G. vaginalis has a highly diverse population structure (17), and cocolonization with multiple strains is common (18); it is possible that one strain predominates at the cervix and the other in the vagina. BVAB2 and vaginal Megasphaera spp.…”
mentioning
confidence: 99%
“…They found that there were four nonrecombining groups of G. vaginalis genomes and proposed that it "may be appropriate to treat these four groups as separate species." Ahmed et al (27) determined that there are 746 genes in the core G. vaginalis genome and that these core genes make up only ϳ52% of the genome sequences, on average. Therefore, going forward, we would derive Homers for each of the four groups separately based upon sequence differences.…”
Section: Discussionmentioning
confidence: 99%
“…While the two reverse primers (conventionally called 1492R) had a perfect match, the two forward primers (conventionally called 8F) had no perfect match to any of the three G. vaginalis genome sequences. Ahmed et al (27) compared the genome sequences of 17 G. vaginalis clinical isolates, most of which they sequenced themselves. They found that there were four nonrecombining groups of G. vaginalis genomes and proposed that it "may be appropriate to treat these four groups as separate species."…”
Section: Discussionmentioning
confidence: 99%